Sero-surveillance of Mycobacterium avium subspecies paratuberculosis infection in ruminants in Medina - Shabana, Iman Ibrahim; Aljohani, Aisha A (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The present study aimed to assess for the first time, in Medina, the prevalence of Mycobacterium avium subsp. paratuberculosis in ruminants due to its potential zoonotic importance. Materials and methods: A total of 823 sera samples and 364 milk samples were used to determine the incidence of Mycobacterium avium subsp. Paratuberculosis (MAP) using the indirect Enzyme-Linked Immunosorbent Assay. Results: The seroprevalence of MAP was 11.1% in sheep and 13.8% in goats, while no infection was recorded among camels. MAP infection was not influenced by the animal’s gender, but it was influenced by its locality since the infection rate in local animals was higher than that in imported ones with a significant correlation (p < 0.05). MAP infection had a significant correlation (p < 0.05) with 2 years aged animals. On the other hand, the detection of MAP in milk revealed that 17 (13.8%) goats and 12 (4.9%) sheep were infected. The prevalence of MAP in milk samples was not influenced by either the animal’s age or locality. Conclusion: Sheep and goats may act as a reservoir for MAP to the Medina community. Since Medina is an active area of mass gatherings as a destination for pilgrims throughout the year, therefore, necessary control measures should be implemented to lower the economic losses, zoonotic infections, and the possibility of a global epidemic. J. Adv. Vet. Anim. Res., 7(1): 69-76, March 2020